2020
DOI: 10.3390/cancers12061556
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Enrichment of Circulating Tumor Cells for Downstream Phenotypic Analysis in Patients with Non-Small Cell Lung Cancer Treated with Anti-PD-1 Immunotherapy

Abstract: The current study aimed at the optimization of circulating tumor cell (CTC) enrichment for downstream protein expression analyses in non-small cell lung cancer (NSCLC) to serve as a tool for the investigation of immune checkpoints in real time. Different enrichment approaches—ficoll density, erythrolysis, their combination with magnetic separation, ISET, and Parsortix—were compared in spiking experiments using the A549, H1975, and SKMES-1 NSCLC cell lines. The most efficient methods were tested in patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…Previous validation studies of the Parsortix PR1 system have shown similar recovery of epithelial cells [11,[18][19][20][21]. The imperfect capture efficiency can be partially attributed to deformation and capillary flow required by the platform resulting in lysis of some CTC.…”
Section: Discussionmentioning
confidence: 88%
“…Previous validation studies of the Parsortix PR1 system have shown similar recovery of epithelial cells [11,[18][19][20][21]. The imperfect capture efficiency can be partially attributed to deformation and capillary flow required by the platform resulting in lysis of some CTC.…”
Section: Discussionmentioning
confidence: 88%
“…PD-L1 expression levels on cancer and/or immune cells have been associated with clinical responses to anti-PD-L1/PD-1 therapy [ 20 ]. The expression of PD-L1 in CTCs, isolated using different approaches, has been extensively investigated and reported in lung cancer [ 21 , 22 ]. PD-L1 was also detected in CTCs from patients with melanoma, breast, prostate and gastrointestinal cancer [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with previous studies highlighting the necessity of the combined use of multiple markers in order to improve the sensitivity of CTC detection in NSCLC, which might be attributed to the high heterogeneity of CTCs identified in lung cancer [ 19 , 21 ]. In a recent comparative study from our group, different manual and automated enrichment approaches were shown to provide divergent CTC detection rates, and complementary clinical information for patients with advanced NSCLC treated with immunotherapy [ 29 ]. Moreover, a discordance between CellSearch and different detection approaches has been extensively reported in NSCLC [ 11 , 30 ].…”
Section: Discussionmentioning
confidence: 99%